2008
DOI: 10.1093/bja/aem342
|View full text |Cite
|
Sign up to set email alerts
|

Sedation and regional anaesthesia in the adult patient

Abstract: This review discusses sedation for regional anaesthesia in the adult population. The first section deals with general aspects of sedation and shows that the majority of patients receiving sedation for regional anaesthesia are satisfied and would choose it again. Methods of assessing the level of sedation are discussed with emphasis on clinical measures. The pharmacology of the drugs involved in sedation is discussed, with propofol and remifentanil appearing to be the combination of choice for sedation in regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(106 citation statements)
references
References 115 publications
4
93
0
9
Order By: Relevance
“…But many patients don't like to be awake to remember or recall the intraoperative procedure [46] and request for some form of sedation. The aim of sedation in regional anaesthesia technique include general patient comfort, freedom from specific discomfort and some amnesia for entire procedure [47].…”
Section: Sedation Under Spinal Anaesthesiamentioning
confidence: 99%
“…But many patients don't like to be awake to remember or recall the intraoperative procedure [46] and request for some form of sedation. The aim of sedation in regional anaesthesia technique include general patient comfort, freedom from specific discomfort and some amnesia for entire procedure [47].…”
Section: Sedation Under Spinal Anaesthesiamentioning
confidence: 99%
“…[9][10][11][12][13][14] Hastaların duyduğu korku ve anksiyeteyi azaltmak, rahatsızlığını hafifletmek, işlemle ilgili toleransını ve konforunu artırmak için benzodiazepinler, propofol, klonidin ve deksmedetomidin gibi alfa2 adrenoseptör agonistleri, sevofluran, ketamin ve opioidler anestezistler tarafından kullanılmaktadır. 4 Bizim çalışmamızda kullandığı-mız midazolam ve deksmedetomidin, metabolitlerinin inaktif olması ve resedasyona yol açmaması nedeniyle 15 uyguladığımız dozlarda hastalarımızın bilinçlerinin iletişim kurulabilecek kadar açık, ancak cerrahi konfor sağlayacak kadar sedatize olmalarını ve aynı zamanda derlenme kalitesinin yeterli olmasını sağlamıştır.…”
Section: Discussionunclassified
“…1 Anesthesiologists must balance patient satisfaction vs the risk of respiratory depression associated with oversedation. A review of closed claims has revealed that respiratory depression from oversedation has caused catastrophic adverse events such as brain damage and death.…”
Section: Résumémentioning
confidence: 99%